Implementation of Multicultural Education at the Al-Qur'an Harsallakum Islamic Boarding School in Bengkulu City - Riska Mardela; Hasrul Piliang; Maria Montessori; Susi Fitira Dewi (GHAITSA : Islamic Education Journal, 2026)
This article aims to analyze the implementation of multicultural education at the Al-Qur'an Harsallakum Islamic Boarding School in Bengkulu City and identify supporting and inhibiting factors in its implementation. This research uses a qualitative approach with a case study type. This research uses a qualitative approach with a case study type of research. The research informants consisted of Islamic boarding school leaders, tutors, and students who were selected purposively. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of multicultural education in Islamic boarding schools is carried out through heterogeneous dormitory-based care, the use of a unified language in communication, the implementation of a student code of ethics, and collective activities that foster values of tolerance and togetherness. Supporting factors for the implementation of multicultural education include inclusive Islamic boarding school leadership, a tolerant social environment, and the integration of religious and social values in the lives of students. The inhibiting factors are related to the dynamics of adaptation of students who come from diverse cultural backgrounds and the complexity of the 24-hour dormitory life system.